Teaching Sam to Read: An Integrated Team Approach with One Child with Autism Spectrum Disorder - Coulter, Gail; Sasnett, Roger (Journal of the American Academy of Special Education Professionals, 2016)
Few evidence-based practices are available to guide educators in teaching reading to children with Autism Spectrum Disorder who have complex learning and behavioral needs associated with the symptoms of ASD and common co-occurring conditions, such as Attention Deficit/Hyperactive Disorder and Specific Learning Disability. Some researchers have suggested aligning interventions with the general learning profile of children with ASD. Other studies recommend using a comprehensive treatment model for behaviors associated with ASD. This case study documents how utilizing a comprehensive approach to address the unique learning profile of one child with multiple neurodevelopmental disorders led to significant gains in that child’s reading achievement. The authors suggest that the combination of interventions for one child with one learning profile may be effective for other children with ASD with a similar constellation of symptoms.